TERAPI MUSIK EFEKTIF DALAM MENURUNKAN KECEMASAN PASIEN PRE OPERASI - Nani Fidayanti; Wenny Savitri; Paulus Subiyanto (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Surgery is one of the medical interventions, which can cause fear, anxiety, and stress due to its effects toward the body and soul integrity. Nurses have significant roles in pre-operative care by helping patients to decrease pre-operative anxiety. One of the methods is by using complementary therapy. The use of music therapy is not common in Indonesia. Therefore, scientific studies to prove the role of this therapy to decrease the level of anxiety of preoperative patients in needed. Objective: To investigate the effects of music therapy in reducing anxiety levels of preoperative patients. Methods: The study was a quasy experimental study with pre and post-test design. The samples were selected with a non-probability sampling along with a purposive sampling technique. The amount of samples in this study was 50 respondents. Results: Statistical test used in this research was paired sample t-tests involved the control and intervention groups. The control group showed the average value of the increased of anxiety level of 0.8 without any intervention of music therapy with t = -1503, df = 24, p <0.05. Whereas the avarage value of the decreased of anxiety level was -5.52 with t=5.081, df=24, p<0.05. Meanwhile the independent t- test results for both groups showed a significant difference between mean value of the anxiety level (t= 3,373, df = 48, p <0.05). Conclusion: Music therapy has a significant effect in reducing preoperative anxiety levels of patients. Keywords: Anxiety, preoperative, music therapy